2005
DOI: 10.1103/physrevb.72.075131
|View full text |Cite
|
Sign up to set email alerts
|

Approximate and exact nodes of fermionic wavefunctions: Coordinate transformations and topologies

Abstract: A study of fermion nodes for spin-polarized states of a few-electron ions and molecules with s, p, d one-particle orbitals is presented. We find exact nodes for some cases of two electron atomic and molecular states and also the first exact node for the three-electron atomic system in 4 S(p 3 ) state using appropriate coordinate maps and wavefunction symmetries. We analyze the cases of nodes for larger number of electrons in the Hartree-Fock approximation and for some cases we find transformations for projecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 28 publications
(31 reference statements)
0
52
0
Order By: Relevance
“…We have developed a new program QWalk for general purpose QMC calculations written in C++ with modern programming techniques and incorporating state of the art algorithms in a fast and flexible code. QWalk has already been used in several publications [3,4,5,6,7,8], and we would like to present a summary of its current capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…We have developed a new program QWalk for general purpose QMC calculations written in C++ with modern programming techniques and incorporating state of the art algorithms in a fast and flexible code. QWalk has already been used in several publications [3,4,5,6,7,8], and we would like to present a summary of its current capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…For the ground state, the number of nodal cells is minimal and Mitas 9 has shown that these systems have the minimal number of two nodal pockets. As explained by Bajdich et al 5 , any distortion of the node from the great circle leads to additional cells which can only increase energy by imposing higher curvature (kinetic energy) on the wave function. This argument has been used by Feynman to demonstrate that the energy of fermionic ground state is always higher than the energy of the bosonic state, and by Ceperley 1 to demonstrate the tiling property of the nodal surface.…”
Section: Proof Of the Exactness Of The Nodesmentioning
confidence: 99%
“…For atoms, it includes two triplet -3 S e (1s2s) and 3 P e (2p 2 ) -and two singlet -1 S e (2s 2 ) and 1 P e (2p 2 ) -states of the helium atom and the three-electron atomic state 4 S(2p 3 ). 4,5,12 The quality of fermion nodes is of prime importance in quantum Monte Carlo (QMC) calculations due to the fermion sign problem, which continues to preclude the application of in principle exact QMC methods to large systems. The dependence of the diffusion Monte Carlo a) Electronic mail: Corresponding author: pf.loos@anu.edu.au b) Electronic mail: dario.bressanini@uninsubria.it (DMC) energy on the quality of the trial wave function is often significant in practice, and is due to the fixed-node approximation which segregates the walkers in regions defined by the trial or guiding wave function.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations